1994
DOI: 10.1007/bf00214154
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the kinetics and bioavailability of pure and soil-adsorbed naphthalene in dermally exposed male rats

Abstract: The aim of this study was to utilize pharmacokinetic techniques to assess the bioavailability of sandy or clay soil-adsorbed naphthalene vs chemical alone following dermal treatment of male rats. Animals were exposed to 43 micrograms total of 14C-naphthalene (pure or adsorbed to one of two soils) introduced into a shallow glass cap covering a 13-cm2 area on the skin of each rat. While both soils delayed the time to reach maximum plasma concentration of radioactivity and significantly increased the half-life of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
22
0
4
Order By: Relevance
“…Our results show that most naphthalene is metabolized to 1-and 2-naphthol and 1,4-naphthoquinone (figure 2). Small amounts of 1-naphthol and 2-naphthol are excreted in the urine after the dermal application of naphthalene (4). In an earlier study it has been shown that there is a good statistical correlation between 1-naphthol excretion and naphthalene exposure in the concelltration range of 0.2-6 mg/m3.…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Inmentioning
confidence: 98%
“…Our results show that most naphthalene is metabolized to 1-and 2-naphthol and 1,4-naphthoquinone (figure 2). Small amounts of 1-naphthol and 2-naphthol are excreted in the urine after the dermal application of naphthalene (4). In an earlier study it has been shown that there is a good statistical correlation between 1-naphthol excretion and naphthalene exposure in the concelltration range of 0.2-6 mg/m3.…”
Section: T T H I S S T U D Y S H O W S T H a T O P E R A T O R S Inmentioning
confidence: 98%
“…Unlike the Turkall et al(1994) and Kadry (1995) studies, the sandy soil with higher organic matter had higher dermal bioavailability. This is probably due to the autoclaving step used in soil preparation which may have broken down the organic matter in the soil.…”
Section: Key In Vitro Dermal Bioavailability Studiesmentioning
confidence: 58%
“…Metabolites of hydroxylated PAH (pyrene, phenanthrene, naphthalene and fluorene) have been analysed by Turkall et al (1994); Elovaara et al, (2006);McClean et al,, (2012); Serdar et al, (2012);and, Choosong et al, 2014). Pliel et al (2000) quantified exposure of marker compounds (e.g.…”
Section: Occupational Human Exposurementioning
confidence: 99%
See 2 more Smart Citations